AKSESIBILITAS ANAK TERHADAP MEDIA : INTERNET SEHAT BAGI ANAK - MACHYUDIN AGUNG HARAHAP; SUSRI ADENI (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
Children have wide access to media in this millennial century. It can be said that most of children are connected to the media, especially the internet. Television is no longer the main medium used by children to get entertainment, but has been replaced by the internet. The overload information that children receive should be accompanied by good information that they can filter. Healthy internet for children is a guide that should be used as a reference for parents in facilitating their children to surf the internet. This is intended so that children can filter information that is really needed for them.